Management of gastrointestinal involvement in scleroderma - Nagaraja, Vivek (Curr Treatm Opt Rheumatol, 2015)
Gastrointestinal tract (GIT) commonly affects patients with systemic sclerosis (SSc). The GI involvement is quite heterogeneous varying from asymptomatic disease to significant dysmotility causing complications like malabsorption, weight loss and severe malnutrition. This review focuses on the management of GI involvement in SSc and has been categorized based on the segment of GIT involved. A brief discussion on the role of patient reported outcome measures in SSc-GI involvement has also been incorporated.